Удосконалення системи управління інформаційною складовою фінансово-економічної безпеки підприємства - Атамас, Олександр Петрович; Atamas, Oleksandr; Майстер, Т. М.; Master, Тaras (Науково-освітній інноваційний центр суспільних трансформацій м. Чернігів, 2023)
В сучасних умовах трансформаційних змін та економічних перетворень безумовним пріоритетом становлення та потенційного розвитку суб’єктів ведення бізнесу є можливості управління системою інформаційних перетворень на усіх рівнях. Інформаційна складова є рушійною силою формування сильних сторін системи інноваційних перетворень підприємства, запорукою його інвестиційної привабливості та прогнозування фінансово-економічного розвитку. Діджиталізація сформувала нові пріоритети для забезпечення фінансово-економічної безпеки підприємств, створюючи передумови для довгострокового стратегічного планування діяльності з урахуванням тактики та стратегії суб’єкту ведення бізнесу. У статті проаналізовано механізми удосконалення системи управління інформаційною складовою крізь призму забезпечення високих показників фінансово-економічної безпеки підприємства, сформовано пріоритетні шляхи розвитку системи управління інформацією при веденні бізнесу з урахуванням сучасних економічних перетворень в світовій економіці The ability to manage the system of information transformations at all levels in modern conditions of transformational changes and economic transformations is an absolute priority for the formation and potential development of busi ness entities. The informational component is the driving force of the formation of the strengths of the system of in novative transformations of the enterprise, the guarantee of its investment attractiveness and forecasting of financial and economic development. Digitalization has formed new priorities for ensuring the financial and economic security оf enterprises, creating prerequisites for long-term strategic planning of activities taking into account the tactics and strategy of the business entity. The article analyzes the mechanisms of improving the management system of the information component through the prism of ensuring high indicators of the financial and economic security of the enterprise, and forms the priority ways of developing the information management system in conducting business, taking into account modern economic transformations in the world economy. Research materials are devoted to the generalization of theoretical foundations in the field of financial and economic security. A content analysis of the in terpretation of the concept of «financial and economic security» through the prism of the management system of the information component of the enterprise was conducted, the need to introduce conceptual approaches to the man agement of information activities, the formation of a complex mechanism for ensuring the formation of information pri orities in business conduct was substantiated. As part of the implementation of the effectiveness of the management mechanism of the information component of the financial and economic security of the enterprise, it is necessary to solve a complex of issues regarding the influence of external and internal environmental factors on business results. Possible prospects for the development of the SMART concept of state policy in the context of today’s globalization transformations are analyzed. Innovation is an integral part of the context of modernization and reorientation of the economy to the possibility of competing with countries with developed economies in the world. In the conditions of the digital economy, the primary task is the formation of priority vectors of economic development in the domestic and foreign markets, strengthening of international positions, and development of state policy in the context of innovation. Key words: management; system; information; financial and economic security; enterprises; mechanism
Improvement of information warehouse management system of financial and economic security of enterprise
Keywords: управління; management; система; system; інформація; information; фінансово-економічна безпека; financial and economic security; підприємства; enterprises; механізм; mechanism